2003
DOI: 10.1021/es026176d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Performances of Membrane Bioreactor and Conventional Activated Sludge Processes on Sludge Reduction Induced by Oligochaete

Abstract: Pilot-scale experiments were carried out to compare sludge reduction induced by Oligochaete in a submerged membrane bioreactor (MBR) and a conventional activated sludge (CAS) reactor for 345 d. Worm growth in the CAS reactor was much better than in the MBR. The average worm density of the aeration tank in the CAS reactor was 71 total worms/mg of volatile suspended solids (VSS), much higher than that in the MBR (10 total worms/mg of VSS). Worms did not naturally produce in the MBR, and the dominant worm type in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
48
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 17 publications
9
48
1
1
Order By: Relevance
“…The average free-swimming worm densities in both the IODVC and the worm reactor were 72 ± 76 and 82 ± 99 no./mgVSS, respectively, and their maximal worm densities occurred on day 58 reaching 211 and 309 no./mgVSS, respectively. The size of A. hemprichi was among 0.5-2 mm, the same as results of literatures [12,15,19]. Compared with previous researches in membrane bioreactor and conventional activated sludge process [12,15,19], the amounts of free-swimming worms in this study as shown in Table 2 were lower than their results, but the free- swimming worm densities, including average and maximal values, were higher than their results.…”
Section: Worm Growthsupporting
confidence: 84%
See 4 more Smart Citations
“…The average free-swimming worm densities in both the IODVC and the worm reactor were 72 ± 76 and 82 ± 99 no./mgVSS, respectively, and their maximal worm densities occurred on day 58 reaching 211 and 309 no./mgVSS, respectively. The size of A. hemprichi was among 0.5-2 mm, the same as results of literatures [12,15,19]. Compared with previous researches in membrane bioreactor and conventional activated sludge process [12,15,19], the amounts of free-swimming worms in this study as shown in Table 2 were lower than their results, but the free- swimming worm densities, including average and maximal values, were higher than their results.…”
Section: Worm Growthsupporting
confidence: 84%
“…During energy transfer from bacteria to higher trophic level organisms, energy is lost due to inefficient biomass conversion and thus the predator may make a large contribution to biomass reduction [2,3]. Recently, many studies have focused on sludge reduction induced by protozoa and metazoa grazing on bacteria [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It is well known that the presence of protozoa and metazoa in aerobic wastewater treatment processes plays an important role in keeping effluent clear by consuming dispersed bacteria and settled solids.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations